Feasibility Analysis of Coeurs De Dieu's Strategy on Developing Poetry Appreciation Material into Short Stories - Wardiah, Dessy; ., Hetilaniar (KnE Social Sciences, 2022)
This study analyzes the feasibility of Coeurs De Dieu’s strategy of converting poetry appreciation material into short stories. The study uses a development research design, and a guide on developing a learning strategy was compiled by the authors. Data were collected using questionnaires, interviews, and performance tests to develop poetry into short stories. In addition, descriptive data on the product development process of Coeurs De Dieu’s strategy such as reviews and suggestions from material, media, language, and user experts were also collected. The results of data analysis in this study were categorized as valid, meaning that the Coeurs De Dieu strategy was feasible to use in learning. Keywords: Coeurs De Dieu, poetry appreciation, short story